Urbanization in the Marmara Basin - Relationship Between the Waste Water and Influences on the Receiving Environment - (:unkn) unknown (MARMARA UNIV, 2016)
Marmara Basin covers 2.96% of area of Turkey with approximately 23 084,6 km2 area. The basin covers entire catchment area of the all rivers that flows to Marmara Sea except Susurluk River. Significant increase in population growt and urbanizaton process in the basin has important effect on water quality just like other environmental problems. In the basin, effect of household waste water on water quality is depend on distribution of population and existence of treatment plant. Household waste water and industrial waste water amounts in especialy Istanbul and Kocaeli province are always higher because of accumulation of population, urbanization and industrializaton on eastward in the basin. Thus, across the basin, Istanbul province comes first and Kocaeli province follows it according to contaminated and under risk of contamination surface water resources. And also rivers of Yalova, Canakkale and Tekirdag provinces located in the basin are contaminated. Other domains of wastewater are, coastal areas of Istanbul province, Gulf of Izmit and Gulf of Gemlik. Municipalities that provides treatment service in Istanbul, Kocaeli and Bursa provinces that located in the basin, especially places located scope of metropolitan municipalities, has higher values than average of Turkey. This situation the basin's wastewater discharge environment has begun to have positive effect on water quality.
Keywords: Marmara Basin; the water quality; urbanization; waste water